Health risk assessment associated with inhalation exposure of carbonyl compounds to gasoline workers in Bangkok, Thailand - Sucot Nopparatbundit (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2010